Mg-1.4 wt%Ca-xwt%Zn 합금의 이단 용체화 및 시효처리에 따른 미세구조 변화와 물성에 관한 연구 - 구성모; Seong Mo Koo; 정하국; Ha Guk Jeong; 김택수; Teak Soo Kim; 김혜성; Hye Sung Kim (대한금속·재료학회지, 53(9), 2015)
Optimum heat treatment conditions to improve the hardness and corrosion resistance of ternary Mg-Ca-Zn alloys have been studied, based on the theoretical models and DSC (Differential scanning calorimetry) experimental data. Two-step heating process at 420 ℃ and 480 ℃ has been applied and we have found that the low melting point phase, Ca2Mg6Zn3 can effectively be dissolved into α-Mg matrix without premature melting. Due to preceding treatment at lower temperature followed by the second stage solid solution heat treatment at 480 ℃, Mg-1.4 wt%Ca-xwt%Zn alloys (x=0, 1.5 and 4.0) exhibit improved corrosion resistance than that from the single step solid solution treated alloy at 480 ℃. However, aging treatment of the alloy at 200 ℃ has led to the homogeneous precipitation of Ca2Mg6Zn3 and Mg2Ca phases in the matrix as well as at the grain boundary. This microstructural change results in the deterioration of corrosion resistance mainly originated from galvanic corrosion between the matrix and the precipitates. The hardness of Mg-1.4%Cax% Zn alloy, on the other hand, significantly increases with Zn addition by applying two-step solid solution and aging heat treatment.